Diel Patterns and Temporal Trends in Spawning Activities of Robust Redhorse and River Redhorse in Georgia, Assessed Using Passive Acoustic Monitoring. Issue 3 (23rd April 2015) - Straight, Carrie A.; Rhett Jackson, C.; Freeman, Byron J.; Freeman, Mary C.
Abstract: The conservation of imperiled species depends upon understanding threats to the species at each stage of its life history. In the case of many imperiled migratory fishes, understanding how timing and environmental influences affect reproductive behavior could provide managers with information critical for species conservation. We used passive acoustic recorders to document spawning activities for two large‐bodied catostomids (Robust Redhorse Moxostoma robustum in the Savannah and Broad rivers, Georgia, and River Redhorse M. carinatum in the Coosawattee River, Georgia) in relation to time of day, water temperature, discharge variation, moonlight, and weather. Robust Redhorse spawning activities in the Savannah and Broad rivers were more frequent at night or in the early morning (0100–0400 hours and 0800–1000 hours, respectively) and less frequent near midday (1300 hours). Spawning attempts in the Savannah and Broad rivers increased over a 3–4‐d period and then declined. River Redhorse spawning activities in the Coosawattee River peaked on the first day of recording and declined over four subsequent days; diel patterns were less discernible, although moon illumination was positively associated with spawning rates, which was also observed for Robust Redhorses in the Savannah River. Spawning activity in the Savannah and Broad rivers was negatively associated with water temperature, and spawning activity increased in association with cloud cover in the Savannah River. A large variation in discharge was only measured in the flow‐regulated Savannah River and was not associated with spawning attempts. To our knowledge, this is the first study to show diel and multiday patterns in spawning activities for any Moxostoma species. These patterns and relationships between the environment and spawning activities could provide important information for the management of these species downstream of hydropower facilities.